Adhesion and bonding properties of malaysian hardwood species after alkaline copper quaternary treatment for cross laminated timber - Adnan, Nur Amira (2020)
The bonding and strength properties of ACQ-treated cross laminated timber (CLT) made of four Malaysian hardwood species, i.e. Batai, Sesendok, Rubberwood and Kedondong were evaluated. The present study was carried out to produce ACQ-treated CLT manufacturing process with good and excellent bonding properties, without compromising their true strength. Three layers of single- and mixed-species CLT were fabricated at three different glue spread rates, i.e. 200 g/m2, 250 g/m2, 300 g/m2, and two different clamping pressure, i.e. 0.7 N/mm2 and 1.4 N/mm2. Each CLT combinations were treated with ACQ at 2 % concentration and compared with untreated group. Block shear strength and delamination tests were carried out in compliance with BS EN 16351: 2015 to examine the bonding performance of the CLT. Two-way analysis of variance (ANOVA) and Least Significant Difference (LSD) test were conducted to evaluate the effects of ACQ and species on density, surface roughness, contact angle of wettability, block shear strength and delamination percentage. The result revealed that the density of each hardwood species were improved after ACQ treatment and notable increments up to 48 % were observed on their surface roughness value. The contact angles of ACQ-treated samples resulting from water and ACQ treatment were low, less than 44°, suggest high wettability rate. Generally, ACQ did not significantly affect the bonding properties of CLT produced. Clamping pressure give no significant effect on bonding properties of CLT while glue spread rate give a notable results between the species. Singlespecies CLT with a higher glue spread rate, i.e. 300 g/m2 glue spread, provided a stronger mean shear bond strength. Among the ACQ-treated single-species CLTs, Rubberwood has the highest mean shear bond strength of 9.06 N/mm2, followed by Kedondong (6.26 N/mm2), Sesendok (5.52 N/mm2) and the weakest was Batai (4.30 N/mm2). The fabrication of mixed-species CLT has improved the overall performance of the CLT. The combination of ACQ-treated Rubberwood- Sesendok-Rubberwood provided the highest mean shear bond strength of 8.05 N/mm2. None of the CLT delaminated after subjected to the delamination test indicates that the behaviour of CLT samples was not influenced by both clamping pressure and glue spread rate. Among the examined species, Rubberwood exhibited the best bonding performance for untreated control and ACQ-treated samples, followed by Kedondong, Sesendok, and Batai. These combined data suggest that under the conditions tested, this study has met the requirements stated in BS EN 16351:2015 standards. By using ACQ, the bonding strength between CLT members was not significantly affected and shows overall better bonding performance compared to untreated group.